An unusual case of bilateral maxillary and mandibular para premolar: a case report. - Sunil Kumar Vishwanath Chanagay; Vikram Singh; Sunil Rao Bantwal; Manjunatha Muniyappa (Tehran University of Medical Sciences, 2013)
The presence of supernumerary teeth is not uncommon in the general population. They occur more frequently in patients with a family history of such teeth. It is rare to find multiple supernumeraries in individuals with no other associated disease or syndrome. There have been very few documented cases of bilateral maxillary and mandibular supernumeraries in the premolar region. An unusual case of a 35-year-old man with six para premolars and complete dentition is presented.